Does process matter? Experimental evidence on the effect of procedural fairness on citizens' evaluations of policy outcomes. Issue 1 (January 2022) - Martin, Aaron; Mikołajczak, Gosia; Orr, Raymond
One of the key factors distinguishing democracies from non-democracies is the process by which political decisions are made. Central to democratic thought is the idea that policy made in a procedurally fair manner is more legitimate than policy that violates central tenets of procedural fairness. A large number of studies from social psychology show that procedural fairness matters in citizens' evaluations of the success and legitimacy of various outcomes. Despite this observation, most political science literature focuses on the outcomes rather than the process of policy-making. Using survey experiments we find that procedural arrangements are an important factor in citizens' judgement of policy outcomes. Specifically, we find that fair procedural arrangements increase outcome legitimacy to the extent that citizens perceive them to be fairer. Our findings suggest that policy-makers need to pay more attention to procedural arrangements when designing policies.